Enhancing public sector employees ’ professional identity: A study using China’s Labor Force Survey data - Xiaotong Ren; Aimin Zhu; Jiao Yu; Chunna Guo (PLoS ONE, 2025)
Public sector employees, as the crucial link between the party, government, and the general public, represent the frontline in safeguarding the interests of the people and providing services to them. They profoundly influence the implementation and execution of national policy directives. Using data from China’s Labor Force Survey and employing a combination of exploratory factor analysis and confirmatory factor analysis, this research constructs an evaluation index system for public sector employees’ Professional Identity. By dividing the evaluation index system into secondary indicators, and utilizing a structural equation standardization model, the study accurately determines the extent to which each level of indicators within the evaluation index system influences Professional Identity. This research provides pathway recommendations to enhance the Professional Identity of public sector employees, with the aim of mitigating occupational burnout and improving the quality of public services.